Selective Binding of Distamycin A Derivative to G-Quadruplex Structure [d(TGGGGT)]4 - Bruno Pagano; Iolanda Fotticchia; Stefano De Tito; Carlo A. Mattia; Luciano Mayol; Ettore Novellino; Antonio Randazzo; Concetta Giancola (Journal of Nucleic Acids)
Guanine-rich nucleic acid sequences can adopt G-quadruplex structures stabilized by layers of four Hoogsteen-paired guanine residues. Quadruplex-prone sequences are found in many regions of human genome and in the telomeres of all eukaryotic organisms. Since small molecules that target G-quadruplexes have been found to be effective telomerase inhibitors, the identification of new specific ligands for G-quadruplexes is emerging as a promising approach to develop new anticancer drugs. Distamycin A is known to bind to AT-rich sequences of duplex DNA, but it has recently been shown to interact also with G-quadruplexes. Here, isothermal titration calorimetry (ITC) and NMR techniques have been employed to characterize the interaction between a dicationic derivative of distamycin A (compound 1) and the [d(TGGGGT)]4 quadruplex. Additionally, to compare the binding behaviour of netropsin and compound 1 to the same target, a calometric study of the interaction between netropsin and [d(TGGGGT)]4 has been performed. Experiments show that netropsin and compound 1 are able to bind to [d(TGGGGT)]4 with good affinity and comparable thermodynamic profiles. In both cases the interactions are entropically driven processes with a small favourable enthalpic contribution. Interestingly, the structural modifications of compound 1 decrease the affinity of the ligand toward the duplex, enhancing the selectivity.